Why not nursing? A systematic review of factors influencing career choice among healthcare students. (16th November 2015) - Wu, L.T.; Low, M.M.J.; Tan, K.K.; Lopez, V.; Liaw, S.Y.
Abstract : Background: A global shortage of healthcare professionals calls for effective recruitment and retention strategies. The nursing profession faces greater staffing shortages compared with other healthcare professions. Identifying these factors for choosing a career in health care is an important step in structuring future nursing recruitment strategies. Aim: This systematic review examined the motivations for choosing a career in health care, then compared them to factors that influence the choice to pursue a career in nursing. Methods: A literature search of the CINAHL, PubMed, Web of Science and Scopus databases for articles published between 2002 and 2013 was conducted. The search included studies that focused on factors influencing career choice among undergraduate medicine, dentistry, pharmacy and nursing students. Results: A total of 29 papers were included in the review. The themes and subthemes that emerged from this review included: (1) intrinsic factors, including a desire to help others and a personal interest in health care, (2) extrinsic factors, such as financial remuneration, job security, professional prestige and job autonomy, (3) socio‐demographic factors such as gender and socio‐economic status, and (4) interpersonal factors, encompassing the influence of family and other professional individuals. Discussion: Healthcare professionals were generally motivated by intrinsic factors. However, public perceptions of nursing as a low‐paying and low‐status job have significantly hindered the participants' choice to pursue it as a career. Conclusion and implications for nursing and/or health policy: Nursing institutions could provide more platforms to help school leavers better understand the nursing career. In turn, hospital administrators could invite parents to nursing career fairs, increase financial remuneration for nurses, and provide decision‐making avenues aimed at recruiting and retaining more nurses.